Risk of childlessness in help-seeking men with Peyronie’s disease—A Swedish longitudinal study - Ralf Kuja-Halkola; Lars Henningsohn; Brendan Zietsch; Henrik Larsson; Martin Cederlöf (PLoS ONE, 2025)
Peyronie’s disease (PD) is a disorder of the penis that is associated with poor mental health, lowered psychosocial- and sexual wellbeing, which may increase the risk of childlessness in men affected by the disorder. Although this is an issue of significant clinical importance, it has not been addressed in research to date. We conducted a longitudinal cohort study based on data from Swedish national registers utilizing a large sample of help-seeking men with PD, along with matched subjects from the general population. We assessed the probability and odds ratio of childlessness, modeled with logistic regressions, and offspring rate ratio, modeled with Poisson regression. We found that the probability of childlessness was somewhat lowered for men with PD aged between 35 and 71 years at end of follow-up. Men with PD aged 35 or less showed slightly elevated probabilities of childlessness. Specifically, odds ratios for childlessness were between 0.5 and 1.0 for men aged above 35, and between 1 and 1.5 for men aged less than 35, although the confidence intervals for increased odds partly included the null. Analyses of men’s rate of offspring showed similar pattern, with higher rate ratios for older men and lower for younger men. Although more research is needed, the findings of this study suggest that clinical urological practice may be enhanced by a proactive discussions about the potential issue of childlessness in younger men with PD.